SWITCHING, ADHERENCE, DISCONTINUATION AND REINITIATION OF STATINS AMONG OLDER ADULTS: A NATIONWIDE COHORT STUDY. (16th November 2018) - Ofori-Asenso, R; Ilomaki, J; Zomer, E; Curtis, A; Korhonen, M; Bell, J; Zoungas, S; Liew, D
Abstract: The effectiveness of statin therapy is undermined by poor adherence. We examined statin adherence, switching, discontinuation and reinitiation among older adults. A total of 49, 380 older adults (mean age, 73.4 years; 54.3% female) who initiated statin therapy between 1 January 2007 and 31 December 2015 were followed until death or 31 December 2016. Adherence was estimated via the proportion of days covered (PDC). Discontinuation (□90 days without statin coverage), reinitiation (statin dispensation between discontinuation and last follow-up) and switching (first change in statin or intensity) and their related factors were assessed using survival analysis. Among the cohort, 57.5% and 34.5% were adherent (PDC ≥0.80) at 6-months and 9-years, respectively. Over a mean follow-up of 5.2 years, 63.6% (n=31, 406) discontinued, of whom 60.4% (n=18, 977) restarted. Moderate- and high-intensity statins were associated with higher discontinuation compared to low-intensity statins. Increasing age, female gender, dementia, malignancies and psychotic illness were associated with lower reinitiation. Diabetes was associated with higher discontinuation as was initiation by a general practitioner. Compared to maintaining the same statin and intensity upon reinitiation, switching statin plus down-titrating intensity (hazard ratio 0.90, 95% confidence interval 0.83–0.98), switching statin plus up-titrating intensity (0.87, 0.79–0.95) and switching statin plus maintaining same intensity (0.89, 0.84–0.95) reduced the likelihood of discontinuation. Changing intensity while maintaining same statin did not reduce the risk of discontinuation. In conclusion, statin adherence is low and discontinuation is high. However, significant proportions of older adults who discontinue statins restart. Reinitiation with a different statin is associated with improved persistence.